Autonomía económico-productiva de la mujer de la parroquia tendales y su contribución al mejoramiento de la calidad de vida familiar - Robles Herrera, Rosa Elizabeth (2018)
The woman is a character who plays a fundamental role in the family and therefore in society, however we must emphasize that the contribution she makes has not been reflected in the value that has been given. As a starting point for this research work, we will enunciate the limited economic-productive autonomy of the women of the Tendales parish and their contribution to the improvement of the quality of family life, which has been violated by the scarce participation to venture into areas that allow to develop their intellectual and manual skills. Although females try to disassociate themselves from the economic dependence that their spouses scarcely provide, they are slowed down to make changes and decide to continue with the paradigm in which they were raised. The objective of the Integrator project is to identify the factors that have prevented women from achieving their autonomy, to insert themselves in productive and socio-economic enterprises that improve their quality of individual and family life, emphasizing the imperative of the ladies to achieve this purpose. Tendales parish, is the field of study that allows us to delve into the context that women develop where the problem exposed is exposed as it is the economic dependence that women have, emerging the idea of creating a productive project to develop skills women, promoting sources of economic income for themselves and their families. To carry out the research, the exploratory method was used, allowing an approach to the object of study, becoming a qualitative approach as it follows a rational-deductive process and the techniques applied are participant observation and interviewing the participants of the group’s nominal made. The main results obtained show that the ladies of the Tendales Parish feel insecure to organize themselves and look for mechanisms that promote their incursion and participation in activities that generate economic resources for their family. That is why the empowerment of the females is of vital importance. The organization and promotion of productive ventures that create employment sources to break into the market and generate income that improves the quality of life of their families. The proposal to solve this problem is aimed at strengthening the innate abilities of the ladies through active participation in the project of entrepreneurship that promotes the economic independence of women. The proposed proposal is aimed at taking advantage of the resources obtained from the sector and that in some cases are discarded, which is why it will not cause severe impacts to the environment but rather will reduce the damages that are now being caused by the disuse, providing this resource. The Tendaleñas women will have the opportunity to promote a quality product to the shrimp companies surrounding the sector and even expand to nearby places offering such production, the cost reduction in the production of the product will generate higher income as the raw material is achieved in the sector.